Infection and Some Aspects of Resistance Mechanism of Capsicum Annuum to Ralstonia Solanacearum - Abdul Rahman, Muhammed (1997)
Bacterial wilt of chilli (Capsicum annuum L.) caused by Ralstonia solanacearum is a major constraint to the production of the crop in Malaysia. To-date very few resistant germplasm of chilli to the pathogen is known. Information on the mechanism of infection and resistance, and multiplication of the pathogen in chilli are lacking. There is also no information on the anatomical characters of the hosts which might be related to resistance. The present study was, therefore, undertaken to obtain this information which would provide an understanding of the disease. It could be useful in formulating wilt-resistance breeding programme in chilli and an effective control measures for the disease. Greenhouse evaluation of the susceptibility of accessions/cultivars of Capsicum spp. to R. solanacearum revealed that the cultivar 'Kulai' was highly resistant. Three accessions were moderately resistant while all others were susceptible to highly susceptible. Anatomical study of resistant and susceptible cultivars showed significant differences in several anatomical characters which may contribute to the limitation of the infection process, movement and multiplication of the pathogen. Population dynamics of the pathogen in susceptible and resistant cultivars revealed that in susceptible cultivar bacterial population did not differ after inoculation, at all sites tested, regardless of inoculation techniques used. Bacterial population differed significantly between cultivars at similar sites tested and for all the techniques used. Bacterial population in stem, root and soil-inoculated resistant plants decreased significantly at all sites. However, when soil-inoculated, the pathogen was not detected from the mid stem only. Thus, the infection was not limited but the resistance may be due to the lower rate of multiplication of the pathogen in resistant plants.